Strategic brand management in function of improving the competitive position of tourist destinations - Daliborka Blazheska; Natasha Ristovska; Dejan Nakovski (UTMS Journal of Economics, 2023)
Creating websites and social media marketing is an integral part of business activities in companies. The Building and managing the brand is the most complex task in the contemporary market and tourism business. Strategic brand management focuses on a brand program that contains a plan for marketing activities for building the tourism brand and its management over time, based on information that will be obtained through constant monitoring and value measurement - the success of the brand in relation to the strategic goals of the tourist destination. This paper emphasizes the Republic of Macedonia as a tourist destination, which as a country should first create prerequisites for its identity and value that will enable a quality performance on the international tourist market. From the research can be concluded that the success of the Republic of Macedonia as an attractive tourist destination is based on the symbiosis of the tourist product and the implementation of appropriate brand strategies that will enable successful positioning in the tourist market.
Keywords: M30; M13; L26; L83; 330; strategic brand management; competitive advantage; tourism destinations; tourism product